Analysis of Benefits and Costs of Transferring Ports of Exports and Imports in Sumatra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The process of exports and imports in the Sumatra region that is carried out through several ports has resulted in the decrease of port’s economies of scale and increase in costs. Efficiency will be obtained if the scale is high by focusing the process of exports and imports of the Sumatra region on the Kuala Tanjung Port. The port development requires an investment of IDR 43 trillion. Based on data in 2019, the decision to determine Kuala Tanjung Port as the only port for exports and imports activities in Sumatra would cause the port to handle exports of 62,607.90 thousand tons, equivalent to 2,871,922 TEU’s. Meanwhile, the port imports volume will be 25,827.3 thousand tons, equivalent to 1,184,738 TEU’s. The ports that have previously been the export gateways will become feeder ports. The related costs are the port investment cost which reaches IDR 43 trillion. Limiting the number of exports and imports gateway ports has the potential to benefit the central government, local government, shipping companies, and road transportation companies.